Ionic liquids as powerful solvent media for improving catalytic performance of silyl borate catalyst to promote Diels-Alder reactions - Kumar, Anil; Pawar, Sanjay S. (Journal of Organic Chemistry, 2007)
[GRAPHICS] Use of the acidic chloroaluminate ionic liquid, including the recycled ones, can improve the catalytic activity of the toluene-coordinated silyl borate in enhancing rates, stereoselectivities, and yields of Diels-Alder reactions.

Isopiestic osmotic coefficients of tetra-n-methylammonium chloride with guanidinium salts at 298.15 k - Kumar, Anil (Journal of Solution Chemistry, 2007)
Isopiestic osmotic coefficients are presented for aqueous mixtures of tetra-n-methylammonium chloride, (CH3)(4)NCl, with guanidinium salts such as GnCl, CH(3)COOGn, GnNO(3), GnClO(4) and Gn(2)SO(4) at 298.15 K up to an ionic strength of 2 mol center dot kg(-1). The osmotic coefficients are analyzed in terms of the Scatchard-Rush-Johnson equations. The activity coefficients of each electrolyte in the mixtures were calculated and fitted by the Harned-type equations. The molar excess Gibbs energy of mixing, Delta(m) G(E), of the mixtures were analyzed with Friedman's equations.
Keywords: aqueous solutions; isopiestic method; Osmotic coefficients; Scatchard-Rush-Johnson equations; tetramethylammonium salts

Insight into the micellization of dodecyldimethylethylammonium bromide (DDAB) in the presence of bovine serum albumin (BSA) - Mehta, S. K.; Bhawna; Bhasin, K. K.; Kumar, Anil (Journal of Colloid and Interface Science, 2008)
in this work, we report the effect of concentration of bovine serum albumin (BSA) on the micellization of a cationic surfactant, doclecyldimethylethylammonium bromide (DDAB). Several samples covering a wide range of concentrations of protein and surfactant have been investigated. The interactions between the moieties are investigated by measuring fluorescence quenching of BSA molecules. The aggregation number of DDAB micelles is found to be small in the presence of BSA. The formation of DDAB-BSA complex is confirmed by FTIR. Absorbance spectroscopy indicates that at higher concentration, the conformational stability of BSA in DDAB is higher. The viscosity data for protein-surfactant systems confirm conformational changes in protein chains induced by the surfactant. The cmc values for DDAB increase with increasing concentration of BSA. At higher temperatures the micellization-complexation becomes enthalpy-dominated. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: Aggregation number; BSA; conductivity; conformational stability; DDAB; FFIR; fluorescence; UV-visible; viscosity

Intramolecular Diels-Alder reaction in ionic liquids: effect of ion-specific solvent friction - Tiwari, Shraeddha; Khupse, Nageshwar D.; Kumar, Anil (Journal of Organic Chemistry, 2008)
The present work aims at understanding the role of viscosity or solvent friction in ionic liquids for an intramolecular Diels-Alder (IMDA) reaction of (E)-1-phenyl-4-[2-(3-methyl-2-butenyloxy)benzylidene]-5-pyrazolone (1). The results have been analyzed on the basis of the current theoretical models, and their failure to account for the observed trends is discussed in terms of ``effective'' viscosity or microviscosity. The rates of the reaction decrease with the increasing viscosity of the ionic liquids. As evident from the anionic effect, the solute-solvent specific interactions play a role in governing the kinetics of the reaction. The lower viscosities of the bistrifluoromethanesulfonimide [NTf(2)](-) based ionic liquids as compared to those based on tetrafluoroborate [BF(4)](-) anion fail to result in a corresponding acceleration in the rates of the reaction. These contradictory results indicate that solvent microviscosity, rather than the bulk macroscopic viscosity, should be the criteria for selecting the ionic liquids as reaction media.

Ionic interactions in aqueous mixtures of hydrophilic and -phobic ions - Kumar, Anil (Pure and Applied Chemistry, 2008)
Ions of both hydrophilic and -phobic nature play a pivotal role in biological systems and during synthesis of many organic molecules. However, the interaction of a hydrophilic ion with a hydrophobic one is not a simple physical process and is useful in understanding the rate enhancement in organic transformations and thermal stability of DNA and RNA. During the talk, an attempt was made to present some of the experimental work on aqueous mixtures of these ions carried out at National Chemical Laboratory, Pune, and give a theoretical interpretation of the binary, ternary, and quaternary interactions operating in these systems. The contribution of these interaction terms to the excess free energy of mixing, Delta(m)G(E), will be analyzed.
Keywords: aqueous solutions; excess free energy; hydrophobic ions; ionic solutions; mixing effects

Ionic liquids: physico-chemical, solvent properties and their applications in chemical processes - Singh, Geetanjali; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2008)
A new class of compounds, called as ionic liquids, has recently emerged as potential substitute for volatile organic solvents. Ionic liquids possess certain special physico-chemical characteristics that render them very useful in different areas of research and development. In this review, the physico-chemical properties and the applications of ionic liquids in chemical processes are critically discussed and recommendations made for probing further the poorly understood aspect of this newly emerging class of compounds.

Interfacial reactivity of ``on water'' reactions in the presence of alcoholic cosolvents - Tiwari, Shraeddha; Kumar, Anil (Journal of Physical Chemistry A, 2009)
A detailed study of the variation in the interfacial reactivity and selectivity of ``on water'' reactions in the presence of increasing amounts of alcoholic cosolvents is discussed in the present work. The initial increase in the rates of ``on water'' reactions on the addition of alcoholic cosolvents is contrary to the sharp decrease in rates observed for homogeneous aqueous reactions. The existing theoretical framework is presented in terms of a typical ``on water'' process to enable a discussion of the experimental observations with reference to changing composition of the reaction medium. On the basis of the interesting observations of reactivity and selectivity variations with composition of the reaction medium, a simple ``signature'' characteristic for ``on water'' reactions is proposed.

Ionic liquids: new materials with wide applications - Khupse, Nageshwar D.; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2010)
Ionic liquids have emerged as possible substitutes for volatile organic solvents and have found many applications in a variety of research areas. In this review, an effort has been made to discuss the special properties of ionic liquids that render these unique solvent media useful in chemical transformations, electrochemical applications, extractions, etc.
Keywords: Chemical processes; Electrochemical devices; ionic liquids; Physicochemical properties; Solvent properties; viscosity

Interesting thermal variations owing to cationic ring structural features in protic ionic liquids - Rai, Gitanjali; Kumar, Anil (Physical Chemistry Chemical Physics, 2013)
The present communication divulges interesting thermal behavior of different protic ionic liquids arising due to the hydrophobicity modifications in their parent cationic ring structures. This work assists us in differentiating between protic ionic liquids, their aprotic counterparts and common electrolytes in water. The thermal signatures produced by protic ionic liquids, aprotic ionic liquids and electrolytes emerge as individual fingerprints for them.

Invoking pairwise interactions in water-promoted diels-alder reactions by using ionic liquids as cosolvents - Manna, Arpan; Kumar, Anil (Chemphyschem, 2014)
Rate constants and derived activation parameters of organic reactions in aqueous media, in particular Diels-Alder reactions, are sensitive to the presence of cosolvents in water. To enhance the solubility window of water, we introduced ionic liquids as cosolvents in the aqueous Diels-Alder reaction between anthracene-9-carbinol and N-ethylmaleimide. The reactive potentials of the organic compounds are parameterized by using semi-empirical quantum chemical methods. The principle of Savage-Wood additivity of group interactions is used to quantify the pairwise group interactions among chemically inert ionic liquids and organic reactants, both at initial and transition states of the reaction. The present approach shows promise, as the use of simple calculations from easily available kinetic data can help researchers to understand the versatility of green ionic-liquid alternatives to volatile organic solvents.

Interesting viscosity changes in the aqueous urea-ionic liquid system: effect of alkyl chain length attached to the cationic ring of an ionic liquid - Nanda, Raju; Rai, Gitanjali; Kumar, Anil (Journal of Solution Chemistry, 2015)
In the present article, we demonstrate the effect of urea on the structure of the ionic liquids in their aqueous solutions through viscometric methods. We unravel the structure altering effect of urea in its aqueous solutions of ionic liquids possessing higher alkyl chains. The finding is an attempt to discern the anomalous behavior of urea as shown in the past with the help of many techniques. Interestingly, in the aqueous solutions of the imidazolium based ionic liquids having substitution of -C4H9 and -C6H13 groups on the imidazolium ring, urea exhibits kosmotropic behavior. Further increase in the substituted alkyl group such as -C8H17 alters the urea behavior to be chaotropic.
Keywords: Alkyl chain length; ionic liquids; Structure-breaker; Structure-maker; Urea; viscosity

Isothermal titration calorimetric study of the ionic liquid solutions in alcohols in extreme dilutions: an investigation of ion-solvent interactions - Rai, Gitanjali; Jain, Preeti; Kumar, Anil (Journal of Solution Chemistry, 2016)
In this work an effort has been made to show the effect of an alcohol-rich environment on imidazolium-based ionic liquids at 298.15 K using an isothermal titration calorimeter. It is divulged from this study that the thermal behavior expressed in terms of excess partial molar enthalpy, \( H_{\text{IL}}^{\text{E}} \), of ionic liquids in various linear alcohols is governed by the increasing hydrophobicity of the residual alkyl group attached to the cation of an ionic liquid and to the alcohol molecules. An interesting observation about the systems consisting of ethylated residuals on both the cations of the ionic liquid and the alcohol molecules is that these systems do not follow the trend exhibited by other ionic liquid–alcohol systems. Interesting information on ionic interactions is obtained by using a simple methodology that gives the enthalpic interaction parameter \( H_{{I{\text{L - IL}}}}^{\text{E}} \).
Keywords: Ionic liquidsAlcoholsExcess enthalpyIsothermal titration calorimeter

Introducing the bipolar solvent media using the aqueous mixtures of amino acid anion-based ionic liquids - Beniwal, Vijay; Kumar, Anil (Journal of Physical Chemistry B, 2017)
To carry out a chemical reaction between the reactants with largely different polarities, it becomes important to have a reaction medium that possesses both the polar and nonpolar solvation environments. In an attempt to explore the reaction media with such unique polarity properties, the present study provides a thorough understanding of the bipolar solvent media using the aqueous mixtures of amino acid anion-based ionic liquids. The highly polar behavior of the binary mixtures used in the study has been ascribed to the pure ionic liquid state. However, the less polar solvation shells have been attributed to the presence of a neutral form of the anions. Addition of water in the amino acid anion-based ionic liquids causes the protonation of a certain fraction of the anions of the ionic liquids, resulting into the formation of a less polar nonionic protonated form along with the highly polar natural anionic form. This results into the formation of two solvation spheres with different polarities, which can be seen very clearly from the presence of two absorption bands (lower wavelength absorption band and higher wavelength absorption band) in the UV-vis absorption spectrum of Reichardt's E-T(30) dye and two emission bands (lower wavelength emission band and higher wavelength emission band) in the fluorescence emission spectrum of C481 dye. The values of the E-T(N) polarity parameter corresponding to the two solvation shells having different polarities have been calculated from the deconvoluted absorption spectra of the Reichardt's E-T(30) and were analyzed in three amino acid anion-based ionic liquids. Generation of the neutral form of anions in the aqueous mixtures formed via a protonation transfer reaction has been confirmed by the H-1 NMR spectroscopy and UV-vis absorption spectrum of 18DHAQ dye. The study also establishes that the Reichardt's E-T(30) dye can be used as a valid polarity probe to study the solvatochromic behavior of the binary mixtures of amino acid-based ionic liquids.